L’entrée en jeu des familles : prélude à la co-construction d’un jeu sérieux sur l’énergie - Dany Lussier-Desrochers; Laurence Pépin-Beauchesne; Marie-Andrée Leduc; Marie-Ève Dupont; Karine Lavigne; Isabelle Simonato; Rosalie Ruel (VertigO)
In Quebec, the government is committed to act on households’ energy efficiency. To materialize this political orientation, a change in the behavior of energy consumers is necessary. Recent studies show that gamification is a promising avenue, creating motivation and commitment to changing energy behaviors. Through a participatory and collaborative method, this study aims to explore how this approach could support Quebec families in adopting behaviors that promote energy efficiency. To do this, a mixed descriptive research design in three phases was used. First, 33 parents completed a questionnaire on their intentions to change and their perceptions regarding the adoption of energy behaviors that can promote better energy efficiency. Based on these results, a game prototype was then developed by experts in the field. During the last phase, dyad interviews (parent-child) were carried out with five families from phase 1 in order to know their prototype impressions. The results obtained show that parents have an interest in developing energy efficiency behaviors to raise awareness among their children. The participants also believe that the use of a game inspired by their daily life would be a relevant and effective way to promote the generalization of what has been learned. The addition of challenges and rewards also seem to be winning game elements for participants. Finally, various proposals for adapting the game were made by the participants.